Eurasianism and the European Far Right : Reshaping the Europe-Russia Relationship - Laruelle, Marlène, 1972- (London : Lexington Books, 2015)
"The 2014 Ukrainian crisis has highlighted the pro-Russia stances of some European countries, such as Hungary and Greece, and of some European parties, mostly located at the far-right of the political spectrum. This book offers a unique insight on the main far-right actors and ideological trends that push, on both sides, for reshaping the Europe-Russia relations and for the emergence of a new pan-European illiberal ideology"--Publisher.
Eurasianism and European far right : reshaping the Europe-Russia relationship / Marlene Laruelle, ed -- Introduction / Marlene Laruelle -- Dangerous liaisons? : Eurasianism, European far right, and Putin's Russia / Marlene Laruelle -- Alexander Dugin's trajectory : mediating European far right to Russia -- Alexander Dugin and the West European new right, 1989-1994 / Anton Shekhovtsov -- Moscow State University's Department of Sociology and the climate of opinion in post-Soviet Russia / Vadim Rossman -- Part II. France, Italy, and Spain : Dugin's European cradles -- A long-lasting friendship : Alexander Dugin and the French radical right / Jean-Yves Camus -- From Evola to Dugin : the neo-Eurasianist connection in Italy / Giovanni Savino -- Arriba Eurasia? : the difficult establishment of neo-Eurasianism in Spain / Nicolas Lebourg -- Part III. Turkey, Hungary, and Greece : Dugin's new conquests -- "Failed exodus" : Dugin's networks in Turkey / Vügar Imanbeyli -- Deciphering Eurasianism in Hungary : narratives, networks, and lifestyles / Umut Korkut and Emel Akçali -- The dawning of Europe and Eurasia? : the Greek golden dawn and its transnational links / Sofia Tipaldou -- Part IV. Conclusions: The European far right at Moscow's service? -- Far-right election observation monitors in the service of the Kremlin's foreign policy / Anton Shekhovtsov.
Includes bibliographical references (pages 245-257) and index.
The Roger Griffin ComFas Collection
Keywords: Dugin, Aleksandr -- Political and social views; Eurasian school; Radicalism -- Europe, Western; Radicalism -- Russia (Federation); Ideology -- Political aspects -- Europe, Western; Ideology -- Political aspects -- Russia (Federation); Europe, Western -- Relations -- Russia (Federation); Russia (Federation) -- Relations -- Europe, Western; Europe, Western -- Politics and government -- 1989-; Russia (Federation) -- Politics and government -- 1991-